Environmental Ethics and Traditional Ethics: Relationship Models - Marek-Bieniasz, Anna (Studia Ecologiae et Bioethicae, 2015)
This article highlights and explains the major models of the relations between environmental ethics and traditional ethics. These models include environmental ethics confronting models with traditional ethics, environmental ethics spacer model relative to traditional ethics, and models indicating the existence of correspondence disciplines. Present in the first phase of the development of environmental ethics, “distancing” in relation to traditional ethics contributed, as can be seen, today, a peculiar relationship between traditional ethics and environmental ethics existed from the very beginning. In a sense, it can be said that thanks to the development of traditional ethics, the development of environmental ethics was possible after some time. Environmental ethics can, therefore, see, inter alia, as a discipline biased against traditional ethics internally (e.g., as a form of ethics detailed, the complementary circle of traditional ethics issues important ecological crisis issues).